Latvian Periodicals about Lithuanian Army Battles in the Vicinity of Daugavpils (June, 1919 – January, 1920) - Soms, Henrichs (Acta humanitarica academiae Saulensis, 2025)
Lithuanian, Polish and Latvian armies participated in driving the Bolsheviks out of the vicinity of Daugavpils. The Latvian press of that time is a serious source for investigating these events. In 1919, 65 editions – newspapers, journals, magazines and bulletins – were published in Latvian. Out of these, the materials from 10 editions have been used in this paper. In order to reflect the events of the battles near Daugavpils, periodicals employed official information sources as well as republished information from other newspapers and magazines. A novel feature in the development of the press was the foundation of Latvian Press Bureau (LPB) “Latopress”. The battles at Daugavpils took place in three phases: August, 1919, September, 1919, and January, 1920. Latvian, Lithuanian, Polish and Red Armies were engaged in them. The information provided by the press on the battles of Lithuanian army at Daugavpils can be relatively classified into several groups. First, newspapers published reports from the General Headquarters of different armies about the advance of the Lithuanian army towards Daugavpils (reaching the border of Kurzeme province in June, 1919; occupying the line of the lakes of Ilūkste – Svente and Medumi; approaching the left bank of the river Daugava; occupying a 25km-wide bank line), and about battles of this army at populated places near Daugavpils (Ilūkste; occupation of Zarasi; battles at Eglaine station; single combats of artillery at Ribaki village and in the direction of Kalkūni; bombardment of Daugavpils). Second, the readers were informed about the collaboration between Lithuanian and Polish armies and their competition in the struggle for the influence in the region as well as in the battles for Daugavpils. Third, newspapers highlighted the opinions of Latvian diplomats about the important role of the Lithuanian army in the battles for Daugavpils, despite the fact that it did not take part in the liberation of the town. At the same time, it should be acknowledged that due to objective reasons (confidentiality of military information) several themes were not discussed by the press, for example, the armament and atmosphere in the Lithuanian army, surnames of unit commanders. However, Latvian newspapers extensively discussed the enemy – armament of the Red Army, atmosphere among commanders and soldiers, and propaganda widely spread by the enemy. At the same time, it should be acknowledged that due to objective reasons (confidentiality of military information) several themes were not discussed by the press, for example, the armament and atmosphere in the Lithuanian army, surnames of unit commanders. However, Latvian newspapers extensively discussed the enemy – armament of the Red Army, atmosphere among commanders and soldiers, and propaganda widely spread by the enemy.